Growth and productivity of zinc-deficient poplar nursery and plantation under differential levels of zinc - Singh, Baljit; Gill, R.I.S. (Indian Journal of Agroforestry, 2020)
Zinc deficiency symptoms appear in poplar nurseries and plantations grown on coarse textured soils as these are low in organic matter and nutrient content. The deficiency is exhibited by development of interveinal yellowing of recently matured leaves (5th or 6th leaf from top of branches or stem) which further extends to lower leaves. The study was conducted to standardize the application of Zn through zinc sulphate to eradicate the deficiency in poplar nursery and plantation. In the nursery, the treatments consisted of six levels of Zn (0, 5, 10, 15, 20 and 25 kg/ha) applied through zinc sulphate heptahydrate in randomized block design in three replications. In poplar plantation, Zn was applied @ 0, 5, 10, 15, 20, 25 and 30 g/plant Zn in 1 m diameter basin during 1st year 0, 10, 20, 30, 40, 50 and 60 g/plant Zn in 2 m diameter basin during 3rd year and 0, 15, 30, 45, 60, 75 and 90 g/plant Zn in respective plots in 3 m strip (1.5 m on each side of tree row) during 5th year. Application of Zn significantly increased growth parameters of poplar nursery and plantation. The lowest collar diameter (2.50 cm) and height (3.96 m) of nursery were observed without Zn application and a significantly higher collar diameter (2.90 cm) and height (4.39 m) with the application of 20 kg/ha Zn. The lowest diameter at breast height, height and timber weight (20.39 cm, 19.46 m and 218.6 kg/plant, respectively) of plantation were observed without Zn application and a significantly higher (21.62 cm, 20.76 m and 261.0 kg/plant, respectively) with the application of Zn @ 20, 40 and 60 g/plant during 1st, 3rd and 5th years, respectively. Therefore, it is advised to apply Zn at the above rates to ameliorate the Zn deficiency in poplar nurseries and plantations.